2011
DOI: 10.1007/s12070-011-0322-7
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Laryngitis in Immunocompetent Patients

Abstract: The diagnosis of fungal laryngitis is often overlooked in immunocompetent patients because it is commonly considered a disease of the immunocompromised. Further confusion is caused by clinical and histological similarity to more common conditions like Leukoplakia. Demonstration of hyperkeratosis particularly if associated with intraepithelial neutrophils on biopsy should trigger a search for fungus using specialized stains. These patients usually present with hoarseness of voice. Pain is present inconsistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 7 publications
1
25
0
2
Order By: Relevance
“…Interestingly, however, there is an increasing number of localized infections reported in immunocompetent hosts . Immunocompetent patients tend to have localized disease without systemic manifestations . Recent published case reports allude to the role of localized immunosuppression, particularly associated with inhaled corticosteroids, as the most significant risk for infection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, there is an increasing number of localized infections reported in immunocompetent hosts . Immunocompetent patients tend to have localized disease without systemic manifestations . Recent published case reports allude to the role of localized immunosuppression, particularly associated with inhaled corticosteroids, as the most significant risk for infection …”
Section: Discussionmentioning
confidence: 99%
“…6,7 Immunocompetent patients tend to have localized disease without systemic manifestations. 8 Recent published case reports allude to the role of localized immunosuppression, particularly associated with inhaled corticosteroids, as the most significant risk for infection. 2,9 Localized cryptococcal laryngitis is an uncommon infection of the larynx, with less than 25 cases reported in the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…3 Amphotericin B used to be the mainstay of treatment 1,12,13 previously, but the azoles especially fluconazole and itraconazole are used widely now. 1,14 Despite a correct diagnosis and appropriate treatment, lack of response is not uncommon. This may be due to thick fungal lesions with central avascularity preventing the antifungals from reaching the site, lack of sensitivity to the prescribed antifungal, or invasive nature of the FL.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of primary laryngeal aspergillosis in a SOT recipient. After an extensive review of the literature, we found other 35 cases of primary laryngeal aspergillosis that have been published in patients with different immune states . We summarize relevant features in Table .…”
Section: Introductionmentioning
confidence: 99%